Artificial Neural Networks Recent Advances, New Perspectives and Applications - Chi Leung Hui, Patrick (Artificial Intelligence, 2023)
This book examines artificial neural networks (ANNs) and their applications in various fields. Chapters address ANNs and deep learning techniques for real-world applications in health care, materials processing, energy management, and more.